PERBANDINGAN SENSITIVITAS AMOXICILLIN DAN ERITROMICIN TERHADAP STREPTOCOCCUS β - HEMOLYTICUS PADA PEROKOK - KARINA RAMADHANI; ANCE ROSLINA (JURNAL ILMIAH SIMANTEK, 2021)
Active smokers and those who have been exposed to cigarette smoke are at high risk for bacterial infection. Exposure totobacco smoke in these cigarettes can increase the susceptibility of upper respiratory tract infections. Knowing thecomparative sensitivity of amoxicillin and erythromycin Streptococcus β-hemolyticus in smokers. Research usingobservational analytic methods. The sample of this study approved 25 samples that met the inclusion criteria determined bypurposive sampling. Data analysis in this study used non-parametric statistics with multivariate analysis with the Wilcoxontest. The average sensitivity of the antibiotic amoxicillin was 17.7188 and the sensitivity of the erythromycin antibiotic was16.7012 with a difference of sensitivity of 1.0176. Wilcoxon test results p = 0.619 (> 0.05) which means there is no significantdifference in the sensitivity of the use of antibiotics amoxicillin and erythromycin against Streptococcus β-hemolyticusbacteria in smokers. There was no significant effect on the use of the antibiotic amoxicillin and erythromycin on Streptococcusβ-hemolyticus in smokers.